Mind the gaps: Assessing and enhancing the trustworthiness of mental health apps - CHAN, Gary Kok Yew (Institutional Knowledge at Singapore Management University, 2022)
Mental health apps including artificial intelligence (“AI”)- powered apps and chatbots have raised serious concerns relating to safety, efficacy and privacy. This article assesses their trustworthiness based on lego-regulatory, ethical and technological measures in addressing the abovementioned concerns. Focusing on applications to mental health apps, it examines Singapore laws, regulations and guidelines relating to software-based and AI medical devices, data protection, consumer protection, advertising and medical negligence. Additionally, upon taking into account other non-binding ethical guidelines, certification standards and technological measures targeted at app developers, a few recommendations are offered for enhancing trust in mental health apps.